The Effect of Halal Label, Brand Image, and Product Quality on the Purchase Decision of Wardah Exclusive Matte Lip Cream Products in Sidoarjo - J.A. Jelita Srikandi Pertiwi; Supriyono Supriyono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Technology, globalization, and social media have changed modern lifestyles, including the need for body care which is now important, especially for women who prioritize a beautiful and confident appearance. This has driven an increase in demand for cosmetics, especially matte lip cream which is popular because of its soft texture and long-lasting. Realizing this trend, Wardah presents an Exclusive Matte Lip Cream with competitive advantages. Sidoarjo, with a Muslim majority and high interest in cosmetics, is an ideal location to study the influence of Halal Label, Brand Image, and Product Quality on Purchasing Decisions. This study aims to determine the influence of the halal label, brand image, and product quality on purchasing decisions for Wardah Exclusive Matte Lip Cream products in Sidoarjo. This type of research is quantitative. Sampling using the purposive sampling method, and the number of samples used was 100 respondents the method used to analyze was the Structural Equation Model (SEM) with the Smart-PLS version 3.0 tool. The tests used were the outer model test, the inner model test, and the hypothesis test. It can be concluded that the halal label (X1), brand image (X2), and product quality (X3) on purchasing decisions (Y) partially have a positive and significant influence.